Lignans from the Leaf of Smallanthus sonchifolius - Xue, Jing-Jiao; Wang, Lan; Chzn, Yong-Kuang; Liao, Zhen; Liu, Wei; Yang, Guang-Yu; Hu, Qiu-Fen (Asian Journal of Chemistry, 2010)
Phytochemical investigation of the leaf of Smallanthus sonchifolius led to the isolation and identification of a new lignan (smallanlignan A) and five known lignans. The structures were elucidated by the analysis of spectroscopic data. The antioxidant activity of smallanlignan A was evaluated and it showed antioxidant activity with an IC50 value of 1.65 μg/mL.